A bibliometric analysis of global research on vitamin D and reproductive health between 2012 and 2021: Learning from the past, planning for the future - Lu, Yimeng; Zhang, Xudong; Wu, Shanshan; Zhang, Siwen; Tan, Jichun (Frontiers in Nutrition, 2022)
Background: Vitamin D plays an invaluable role in reproductive health, but vitamin D insufficiency and deficiency are generally common among couples of childbearing age and pregnant women. This study aimed to evaluate the evolution, development trend, and research hotspot of publications on vitamin D and reproductive health. Methods: The literature on vitamin D and reproductive health between 2012 and 2021 was retrieved from the Web of Science Core Collection. We used VOSviewer and CiteSpace to analyze publication years, countries, institutions, journals, highly cited authors and publications, and co-occurrence and citation bursts of keywords. Results: A total of 1,828 articles and reviews on vitamin D and reproductive health published between 2012 and 2021 were identified. The annual publication outputs showed steady growth, with the most publications (272) and citations (7,097) in 2021. The United States contributed the most publications (458) and had the highest h-index (58). In terms of the number of publications and h-index, the journal named Nutrients ranked first. Nutrition dietetics, obstetrics gynecology, and endocrinology metabolism were three well-represented disciplines in research on vitamin D and reproductive health. Hollis BW, Wagner CL, and Litonjua AA were the top three most productive authors in this field during the last decade. Apart from vitamin D, the five keywords with the most frequent occurrence were vitamin D deficiency, pregnancy, risk, vitamin D supplementation, and 25-hydroxyvitamin D. Keyword citation burst analysis revealed that low birth weight, adipose tissue, marker, and embryo had a citation burst lasting until 2021. Conclusions: In conclusion, vitamin D has received continuous attention in the field of reproductive health, and there appears to have a higher level of research in North America. Multidisciplinary intersection contributed to the in-depth exploration in this field. And the effect of maternal vitamin D levels on fetal lipid metabolism and the prediction of fertility by vitamin D-related markers might be hotspots for the research.